HUBUNGAN KADAR GLIAL FIBRILLARY ACIDIC PROTEIN (GFAP) SERUM DENGAN LUARAN KLINIS NEUROLOGIS PASIEN STROKE HEMORAGIK - Theodorus Kevin Hendartono; Retnaningsih Retnaningsih; Amin Husni (PERDOSNI, 2018)
THE CORRELATION BETWEEN SERUM LEVELS OF GLIAL FIBRILLARY ACIDIC PROTEIN (GFAP) WITH NEUROLOGICAL CLINICAL OUTCOME OF HEMORRHAGIC STROKE PATIENTABSTRACTIntroduction: Glial fibrillary acidic protein (GFAP) is a protein that is responsible for the cytoskeleton structure of glial cells. Increased level of GFAP can be used to predict the level of glial cells damage that accompanies a hemorrhagic stroke. National Institute of Health Stroke Scale (NIHSS) and modified Rankin Scale (mRS) are the measurement scales that have high validity and reliability for determining the long-term functional clinical output of hemorrhagic stroke patients.Aims: To determine the correlation between serum levels of GFAP with neurological clinical outcome of hemorrhagic stroke patients.Methods: Prospective cohort study were conducted at Dr. Kariadi Hospital Semarang in the period of July- November 2018. Serum blood sampling for GFAP examination was carried out in less than 72 hours from the stroke onset. Then the third and seventh day NIHSS and 30-day mRS were assessed. Statistical analyses were performed to assess the correlation between serum levels of GFAP with neurological clinical outcome of hemorrhagic stroke patients.Results: The study found 33 subjects of hemorrhagic stroke patients. Multivariate analysis showed that the serum GFAP levels were significant for NIHSS changes (p=0.003; OR=1.397). Significant differences were also obtained at serum GFAP levels with 30-day mRS (p=0.009; OR=1.603).Discussion: Serum GFAP levels taken in less than 72 hours from the hemorrhagic stroke onset are associated with neurological clinical outcome of hemorrhagic stroke patients.Keywords: Glial fibrillary acidic protein, hemorrhagic stroke, modified Rankin Scale, National Institute of Health Stroke ScaleABSTRAKPendahuluan: Glial fibrillary acidic protein (GFAP) merupakan protein yang bertanggung jawab terhadap struktur sitoskeleton dari sel glia. Peningkatan kadar GFAP dapat digunakan untuk memprediksi tingkat kerusakan sel glia yang menyertai stroke hemoragik. National Institute of Health Stroke Scale (NIHSS) dan modified Rankin Scale (mRS) merupakan skala pengukuran yang memiliki validitas dan reliabilitas yang tinggi untuk penentuan luaran klinis fungsional jangka panjang pasien stroke hemoragik.Tujuan: Mengetahui hubungan kadar GFAP serum dengan luaran klinis neurologis pasien stroke hemoragik.Metode: Penelitian kohort prospektif yang dilakukan di RSUP Dr. Kariadi Semarang selama bulan Juli-November 2018. Pengambilan sampel darah serum untuk pemeriksaan GFAP dilakukan dalam <72 jam pertama onset stroke. Kemudian dinilai skor NIHSS hari ketiga, NIHSS hari ketujuh dan mRS hari ke-30. Data diolah dan dilakukan analisis statistik untuk menilai hubungan kadar GFAP serum dengan luaran klinis neurologis pasien stroke hemoragik.Hasil: Pada penelitian didapatkan 33 subjek pasien stroke hemoragik. Analisis multivariat didapatkan kadar GFAP serum bermakna secara signifikan terhadap perubahan NIHSS (p=0,003; RO=1,397). Perbedaan yang bermakna secara signifikan juga diperoleh pada kadar GFAP serum dengan mRS 30 hari (p=0,009; RO=1,603).Diskusi: Kadar GFAP serum yang diambil <72 jam pertama onset stroke hemoragik berhubungan dengan luaran klinis neurologis pasien stroke hemoragik.Kata kunci: Glial fibrillary acidic protein, modified Rankin Scale, National Institute of Health Stroke Scale, stroke hemoragik